Financial accounting theory I : issues and controversies - Zeff, Stephen A.;Keller, Thomas F. (New York : McGraw Hill Education, 1973)
In 1963, when we were compiling the first edition of this volume of edited readings, it was not usual in most universities to complement textbooks with articles drawn from the periodical literature. One of our objectives was to enable students and teachers to interweave critical and argumentative articles with standard textbook presentations in undergraduate and graduate courses. A second volume was added in 1969. These two volumes, together with readings books edited by others, have, we believe, encouraged many instructors to broaden their approaches to the subject and to make more extensive use of controversial writings.
1. Introduction -- 2. Problems Confronting the Accounting Profession -- 3. Income Determination: Generally -- 4. Valuation of Short-Live "tangible" Cost Factors -- 5. Valuation of Long-Live "tangible" Cost Factors -- 6. Goodwill, Other Intangibles -- 7. Nature Liabilities -- 8. Problems Confronting the Accounting Profession: Proposed Needs.
Includes bibliographical references.
Keywords: ACCOUNTING